Park : The main exhibition of Momentum - Nordic Festival of Contemporary Art 2000 : Momentum. - Momentum - Nordic Festival of Contemporary Art, 2000; Aho, Björn; Baumgartner, Stig; Blom, Ina; Boeskov, Jakob, S.; Bradley, Will; Brinch, Jes; Carlsson, Ulf Verner; Einarsson, Gardar Eide; Ekeberg, Jonas; Fabricius, Jacob; Fetveit, Arild; et al. (Moss, 2000)
Alveng, Dag ; Askeir, Yon Egil ; BAR ; Berg, Lene ; Boeskov, Jakob S. ; Carlsson, Ulf Verner ; Edström, Anders ; Einarsson, Gardar Eide ; Fabricius, Jesper ; Finn, Maria ; Gislason, Olafur ; Hardarson, Kristinn G. ; Heikinaho, Minna ; Hakansson, Henrik ; Jakobsen, Klaus Thejll ; Klingberg, Gunilla ; Kolding, Jakob ; Korkeila, Jukka ; Larsson, Annika ; Lehtonen, Henrietta ; Lindberg, Maria ; Maasalo, Mikko ; Mallander, J.O. ; Melgaard, Bjarne ; Niskanen, Pekka ; Nygren, Anneli ; Olesen, Henrik ; OLO ; Olofsson, Anneè ; Knud, Rasmus ; Rekula, Heli ; Renvall, Seppo ; Rodland, Torbjorn ; Rönicke, Pia ; Sander, François Bucher & Katya ; Seidler, Michelle Eistrup & Marika ; Sigurdardóttir, Katrín ; Sjovoll, Vibeke ; Saethre, Borre ; Sorensen, Elin T.
Momentum - Nordic Festival of Contemporary Art, 2000
Engels
boek